Evaluation of postoperative analgesia and catecholamine levels in laparoscopic cholecystectomy after injection of intraperitoneal bupivacaine - Bayar, M.; Ilhan, Y.; Onal, A.; Akkus, M.; Cifter, C. (My University, 1998)
In this study, our objective was to evaluate the efficacy of intraperitoneal bupivacaine injection on stress response and postoperative analgesia in laparoscopic cholecystectomy. Twenty patients of ASA I classification were included in the study. Intraperitoneal single dose 1 mg/kg bupivacaine in 50 ml of saline solution was administered to group I patients while group II patients were treated with the same doses of drug intraperitoneally by infusion through a catheter. Pain intensity, catecholamine levels, blood gas analysis and haemodynamic parameters were monitorised during the early postoperative period. Group II patients' pain scores were significantly higher (p<0.05) when compared to group I patients'. Significant increases in the catecholamine levels, particularly in adrenaline levels, were detected in the group II. Blood glucose levels increased in both groups while the heart rate values were higher in group II patients at late postoperative period. We believe that bolus intraperitoneal bupivacaine administration is an effective, reliable and noninvasive technique for relieving postoperative pain in laparoscopic cholecystectomy.
Laparoskopik kolesistektomilerde intraperitoneal bupivakain uygulamasinin postoperatif agri ve katekolamin duzeylerine etkileri
Keywords: Bupivacaine; Catecholamine; Laparoscopic cholecystectomy; Postoperative analgesia